In-depth review 2024 (Publications Office of the European Union, 2024)
This in-depth review (IDR) analyses the evolution of Sweden's vulnerabilities related to the real estate market and high private debt and - possibly - newly emerging risks. This year's IDR, which follows the 2024 Alert Mechanism Report (AMR) published in November 2023, assesses the persistence or unwinding of the vulnerabilities identified last year, potential emerging risks, and relevant policy progress and policy options that could be considered for the future. Sweden's economy contracted in 2023 due to rising interest rates and high inflation and is set to broadly stabilise in 2024. High inflation and the subsequent monetary policy tightening, combined with the prevalence of variable interest rates and high household debt, pushed down household consumption and housing construction. Housing construction in the rental sector also suffered from the stricter financial conditions for commercial real estate (CRE) companies. Overall investment is estimated to have decreased by 1.2% in 2023, driven by a decline in housing construction.
10.2765/210059
Keywords: Graue Literatur; macroeconomics; euro area; loan; financial stability; financial supervision; household consumption; gross domestic product; inflation; energy policy; economic forecasting; Sweden; report